2022
DOI: 10.1007/s11747-022-00865-8
|View full text |Cite
|
Sign up to set email alerts
|

An extended health belief model for COVID-19: understanding the media-based processes leading to social distancing and panic buying

Abstract: Building on the health belief model (HBM), this research tests, over six months, how the exposure to COVID-related information in the media affects fear, which in turn conditions beliefs about the severity of the virus, susceptibility of getting the virus, and benefits of safety measures. These health beliefs ultimately lead to social distancing and panic buying. As a first contribution, we find that fear is not directly triggered by the objective severity of a crisis, but rather formed over time by the way in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 57 publications
(154 reference statements)
0
6
0
Order By: Relevance
“…The protection motivation theory (PMT) [ 71 ] and health belief model (HBM) [ 72 ] have been commonly applied in the literature to understand how consumers alter their behavior in response to external factors that are believed to pose risk to their health [ 73 , 74 ]. Since the COVID pandemic began, these theories have been extensively used to study abnormal buying behavior of consumers, more specifically panic buying [ 27 , 75 ]. Outside of panic buying, which is considered to be irrational consumer behavior, these theories can be useful in exploring adaptations in buying behaviors in general.…”
Section: Consumer Adoption Of Online Grocery Shopping: Theoretical Mo...mentioning
confidence: 99%
“…The protection motivation theory (PMT) [ 71 ] and health belief model (HBM) [ 72 ] have been commonly applied in the literature to understand how consumers alter their behavior in response to external factors that are believed to pose risk to their health [ 73 , 74 ]. Since the COVID pandemic began, these theories have been extensively used to study abnormal buying behavior of consumers, more specifically panic buying [ 27 , 75 ]. Outside of panic buying, which is considered to be irrational consumer behavior, these theories can be useful in exploring adaptations in buying behaviors in general.…”
Section: Consumer Adoption Of Online Grocery Shopping: Theoretical Mo...mentioning
confidence: 99%
“…In simple terms, the members of echo chambers only learn one side of the story. To support their point, Lantz and Shaw explain that right-wing extremist online spaces present only the side of the argument that "glorif[ies] and gamif[ies] acts of extreme violence" (p. 16) To counter this phenomenon, recent research has shown the virtuous effects of developing strong critical thinking skills about media content, which robustly reduce maladaptive persuasion (Radanielina Hita et al 2022). Frazer (2023) answers this call by using a well-established framework, selective moral disengagement (SMD), to better comprehend the messages published in the Islamic State's magazine Rumiyah.…”
Section: The Common Ground: the Omnipresence Of Social Mediamentioning
confidence: 99%
“…Although some scales have been developed to be used in different studies researching the predictors of the behavior (e.g., Coroiu et al 2020, The Khoa et al 2021) only a few of them are based on theoretical backgrounds such as Health Belief Model or Theory of Planned Behavior (Beeckman et al 2020, Adiyoso and Wilopo 2021, Gibson et al 2021, Yu et al 2021, Hita et al 2023). The authors have identified a severe defiency regarding the assessment of the physical distancing behavior by using a comprehensive model such as IBM.…”
Section: Introductionmentioning
confidence: 99%